2020
DOI: 10.1002/ijc.33406
|View full text |Cite
|
Sign up to set email alerts
|

Additive value of transarterial embolization to systemic sirolimus treatment in kaposiform hemangioendothelioma

Abstract: Kaposiform hemangioendothelioma (KHE) is a rare vascular tumor in children, which can be accompanied by life‐threatening thrombocytopenia, referred to as Kasabach‐Merritt phenomenon (KMP). The mTOR inhibitor sirolimus is emerging as targeted therapy in KHE. As the sirolimus effect on KHE occurs only after several weeks, we aimed to evaluate whether additional transarterial embolization is of benefit for children with KHE and KMP. Seventeen patients with KHE and KMP acquired from 11 hospitals in Germany were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Occasionally, the spindled tumor cells can demonstrate a swirling growth pattern, invoking a somewhat glomeruloid appearance. Tumor cells have uniform hyperchromatic spindled nuclei arranged in short fascicles with slit-like vascular lumina surrounded by a dense collagenous stroma ( Figure 2 ) [ 6 , 7 , 8 , 9 , 10 , 11 ]. Additionally, most cases show extravasated red blood cells, single cells with lumina containing RBCs, dilated lymphatic vessels, eosinophilic bodies, and hemosiderin amidst vascular cells and fibrin thrombi.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Occasionally, the spindled tumor cells can demonstrate a swirling growth pattern, invoking a somewhat glomeruloid appearance. Tumor cells have uniform hyperchromatic spindled nuclei arranged in short fascicles with slit-like vascular lumina surrounded by a dense collagenous stroma ( Figure 2 ) [ 6 , 7 , 8 , 9 , 10 , 11 ]. Additionally, most cases show extravasated red blood cells, single cells with lumina containing RBCs, dilated lymphatic vessels, eosinophilic bodies, and hemosiderin amidst vascular cells and fibrin thrombi.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, deeper and more extensively infiltrative tumors not amenable to a conservative excision continue to present a conundrum. A review of the current literature has demonstrated several studies in which conservative radiotherapy [ 63 ] or the use of targeted drugs (e.g., Telatnib and Sirolimus) [ 7 , 11 ] provides excellent outcomes for patients, demonstrated by high regression rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the long treatment course and high rate of side effects prompt us into seeking other therapeutic alternatives ( 6 8 ). Transarterial embolization (TAE) has been introduced to manage KMS for about 20 years, with decent results in experienced hands ( 9 , 10 ). We have previously analyzed the clinical features of 16 neonates with KMS and found that TAE had a good effect in some neonates ( 11 ).…”
Section: Introductionmentioning
confidence: 99%